The effect of Galantamine on sleep quality in Thai Alzheimer's disease patients - Chankrachang S. (2014)
Objective: To study the effect of Galantamine on sleep quality in Thai Alzheimer's disease (AD) patients with or without cerebrovascular disease. Material and Method: A 6 month,multicenter, open-label, uncontrolled trial was undertaken in 75 mild to moderate Alzheimer's disease patients with or without cerebrovascular disease. Eligible patients received a flexible-dose of Galantamine 16 or 24 mg/day for 24 weeks. The Pittsburgh Sleep Quality Index (PSQI ) with self-analysis questionnaires were used to evaluate sleep quality. Analyses were based on the intent-to-treat population. Results: Seventy-five eligible patients with mild to moderate Alzheimer's disease with or without cerebrovascular disease (male:female = 32:43, age range 74.5 ± 0.9) were included and 58 patients (79%) completed the present study. The global PSQI scores showed some improvement over baseline (week 0 = 5.10 ± 3.08, week 4 = 4.37 ± 2.48, week 8 = 4.65 ± 2.71 week 24 = 3.70 ± 2.12) but were not yet statistical significant. In contrast, most of each component scores such as sleep quality, sleep latency, sleep duration, sleep disturbances, sleep medication, and daytime dysfunction except sleep efficiency, showed significant differences from baseline after week 8. Moreover, there were no significant differences in global PSQI and component scores between mild and moderate stages of Thai AD patients or between men and women patients. Conclusion: The result of the present study may be consistent with Galantamine being safe and can maintain good sleep quality for mild to moderate Thai AD patients with or without VaD. Galantamine doses of 16-24 mg/day were well tolerated.